2020
DOI: 10.1097/md.0000000000022827
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the neutrophil-to-lymphocyte ratio with distal cholangiocarcinoma patients

Abstract: Background: The present study aimed to investigate the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) in distal cholangiocarcinoma (DCC) following radical surgery. Methods: The clinicopathological data of 59 patients with DCC were retrospectively reviewed. Patients were treated by radical surgery and diagnosed by postoperative pathology at the Second Affiliated Hospital of Kunming Medical University (Yunnan, China), between July 2015 and December 2017. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Other studies propose additional factors, such as a prognostic factor, to improve prognosis in dCCA. Ji et al found that neutrophil-to-lymphocyte ratio (NLR) was associated with poor prognosis ( 33 ). Furthermore, the cancer biomarker, serum carbohydrate antigen 19–9, used as a prognostic factor for poor survival of dCCA patients correlated well with regional lymph node metastases ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies propose additional factors, such as a prognostic factor, to improve prognosis in dCCA. Ji et al found that neutrophil-to-lymphocyte ratio (NLR) was associated with poor prognosis ( 33 ). Furthermore, the cancer biomarker, serum carbohydrate antigen 19–9, used as a prognostic factor for poor survival of dCCA patients correlated well with regional lymph node metastases ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as inclusion of DOI and number of lymph node metastasis is concerned, the verdict is still out ( 29 32 ). There has, however, been increasing studies proposing revisions of the updated 8th edition and alternative staging systems for classification ( 33 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 111 studies were further vetted for eligibility after the titles and abstracts were reviewed. Ultimately, 20 studies were included in the analysis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies identified the PLR as an independent predictor for impaired OS in patients with CCA [ 22 , 28 , 29 , 33 , 34 , 36 , 38 , 41 ], while the PLR was not prognostic for OS in twelve studies [ 23 , 24 , 25 , 26 , 27 , 30 , 31 , 32 , 35 , 37 , 39 , 40 ]. The combined analysis of all twenty publications showed that the PLR values higher than the defined cut-off values predicted a worse OS (HR = 1.14, 95% CI = 1.06–1.24, p < 0.01) with high heterogeneity (I 2 = 55%, p < 0.01, Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation